2012
DOI: 10.5194/amt-5-439-2012
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of the Active Temperature, Ozone and Moisture Microwave Spectrometer (ATOMMS) cm and mm wavelength occultation instrument

Abstract: Abstract. We present initial results from testing a new remote sensing system called the Active Temperature, Ozone and Moisture Microwave Spectrometer (ATOMMS). ATOMMS is designed as a satellite-to-satellite occultation system for monitoring climate. We are developing the prototype instrument for an aircraft to aircraft occultation demonstration. Here we focus on field testing of the ATOMMS instrument, in particular the remote sensing of water by measuring the attenuation caused by the 22 GHz and 183 GHz water… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…In particular, measurements at high values of precipitable water (> 3 cm) are required to constrain the self-broadened continuum. For instance, recent opacity measurements performed with the radio occultation active spectrometer ATOMMS (Active Temperature, Ozone Moisture Microwave Spectrometer, Kursinski et al, 2012) have shown two spectral discrepancies (Kursinski et al, 2016). The first discrepancy is a poor match between the Liebe-MPM93 model and the measured line shape within 4 GHz of the 183.31 GHz line center.…”
Section: On the Radiative Transfer And The Spectroscopymentioning
confidence: 99%
“…In particular, measurements at high values of precipitable water (> 3 cm) are required to constrain the self-broadened continuum. For instance, recent opacity measurements performed with the radio occultation active spectrometer ATOMMS (Active Temperature, Ozone Moisture Microwave Spectrometer, Kursinski et al, 2012) have shown two spectral discrepancies (Kursinski et al, 2016). The first discrepancy is a poor match between the Liebe-MPM93 model and the measured line shape within 4 GHz of the 183.31 GHz line center.…”
Section: On the Radiative Transfer And The Spectroscopymentioning
confidence: 99%
“…In that experiment, the atmosphere was well mixed and nearly homogeneous along the observation path such that the retrieved 20 changes in water vapor from ATOMMS matched those observed with an in situ sensor near one end of the path to 1-2% [Kursinski et al, 2012]. Based on these results, our intent had been to validate these ATOMMS moisture retrievals in the presence of clouds and rain via comparison with independent in-situ moisture measurements analogous to the ~1% validation of clear sky ATOMMS retrievals along a shorter path demonstrated by Kursinski et al [2012]. However, we came to realize that quantitative validation of the ATOMMS water vapor retrievals for this mountaintop experiment was 25 limited by the substantial spatial inhomogeneity of the moisture field itself associated with a longer path, over mountainous terrain, during thunderstorm activity.…”
Section: Validation Against In-situ Measurementsmentioning
confidence: 82%
“…2) using a least squares method. To forward model the clear sky atmospheric attenuation, we used the am Atmospheric Model, version 7.2 [Paine, 2011] which was shown to fit the ATOMMS measurements to the 0.3% level in previous work with the ground-based ATOMMS prototype system [Kursinski et al, 2012]. In operation, the ATOMMS ratio, R in Eq.…”
Section: Interpretation Of Measurementsmentioning
confidence: 99%
“…A range of feasibility studies and technology projects for LMO instruments, and onground demonstration experiments, have evidenced that also the required accuracy and stability is achievable (ESA 2004;Kursinski et al 2012;Liu et al 2017, and references therein). Figure 7 illustrates example performance results for pressure, temperature, and humidity profiling from quasi-realistic end-to-end simulations, accounting for the effects of instrumental errors, clouds, and scintillation noise from turbulence Kursinski et al 2009).…”
Section: Measurement Capabilitiesmentioning
confidence: 99%
“…6 Schematic view of the LMO (red signal paths) and GRO (GNSS RO, with GPS and Galileo systems named as example; green signal paths) occultation event geometry (top panel), and schematic view of the retrieval processing chain for LMO (right) and GRO (left) data (bottom panel). Source Schweitzer et al (2011) Spectrometer (Kursinski et al 2009(Kursinski et al , 2012 and the LMO component of ACCURATEAtmospheric Climate and Chemistry in the UTLS Region And climate Trends Explorer Schweitzer et al 2011). The unique potential of LMO strongly suggests that this ongoing work toward demonstration missions should lead to launches of such first missions in the 2020-2022 timeframe.…”
Section: Microwave Occultationmentioning
confidence: 99%